Colliding Alfvénic wave packets in magnetohydrodynamics, Hall and kinetic simulations. (20th February 2017) - Pezzi, O.; Parashar, T. N.; Servidio, S.; Valentini, F.; Vásconez, C. L.; Yang, Y.; Malara, F.; Matthaeus, W. H.; Veltri, P.
Abstract : The analysis of the Parker–Moffatt problem, recently revisited in Pezzi et al. ( Astrophys. J., vol. 834, 2017, p. 166), is here extended by including Hall magnetohydrodynamics and two hybrid kinetic Vlasov–Maxwell numerical models. The presence of dispersive and kinetic features is studied in detail and a comparison between the two kinetic codes is also reported. Focus on the presence of non-Maxwellian signatures shows that – during the collision – regions characterized by strong temperature anisotropy are recovered and the proton distribution function displays a beam along the direction of the magnetic field, similar to some recent observations of the solar wind.